ANALISIS KELAYAKAN USAHA TANI CABAI MERAH DI LAHAN PASIR PANTAI KECAMATAN PANJATAN KABUPATEN KULON PROGO - Waldi Waldi (Fakultas Pertanian UST, 2017)
This study was conducted in Desa Bugel, Kecamatan Panjatan, Kabupaten Kulon Progo on January-February 2016. This study aimed to investigate the income and farming appropriateness of red chili in Kecamatan Panjatan, Kabupaten Kulon Progo. The method of sampling in this study applied the simple random sampling in the number of 30 red chili farmers. Meanwhile, the method of choosing population in this study utilized purposive sampling. Analysis. Data were analyzed using analysis of cost, analysis of receipt and analysis of income whereas the hypothesis testing used t-Test to assess statistical appropriteness of red chili farming. The result of this study showed that the total number of cost average in red chili farming per season achieved Rp 14 585 467,6 or Rp 51 478 912,8 per hectare, whereas the total number receipt average in red chili farming per season achieved Rp 40 696 905 or Rp 143 703 763 per hectare, and the average of income per farming was Rp 26 111 437.4 or Rp 92 224 850,2. Meanwhile the hyphothesis assessment showed R/C ratio > 1 that was 2,79 and t-Test showed the significant result, thus the red chili farming in Kecamatan Panjatan was appropriate to cultivate.Keyword: red chili, income, analysis of appropriateness